2011
DOI: 10.1007/s10549-011-1365-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms in CD166/ALCAM gene associated with increased risk for breast cancer in a Chinese population

Abstract: Activated Leukocyte Cell Adhesion Molecules (ALCAM, also called CD166, MEMD) are cell surface immunoglobulins that are considered to be prognostic markers for breast cancer. CD166/ALCAM has gained increasing attention because of its significant association with tumor progression and the metastatic spread of breast cancer. Two polymorphisms have been identified in the CD166/ALCAM gene: 5'UTR C/T (rs6437585) and 3'UTR A/G (rs11559013). We analyzed the genotypes of 1033 individuals with breast cancer, and 1116 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…We recently showed that the minor allele of CD44 rs187116 predicts decreased TTR and OS in patients with localized gastric adenocarcinoma (10). More recently, Zhou and colleagues analyzed 2 polymorphisms in ALCAM Additional experiments showed that the T allele was associated with a higher transcriptional activity of the ALCAM gene (26). Both polymorphisms, CD44 rs187116 and ALCAM rs6437585, did not show any clinical associations in this study.…”
Section: Discussioncontrasting
confidence: 50%
“…We recently showed that the minor allele of CD44 rs187116 predicts decreased TTR and OS in patients with localized gastric adenocarcinoma (10). More recently, Zhou and colleagues analyzed 2 polymorphisms in ALCAM Additional experiments showed that the T allele was associated with a higher transcriptional activity of the ALCAM gene (26). Both polymorphisms, CD44 rs187116 and ALCAM rs6437585, did not show any clinical associations in this study.…”
Section: Discussioncontrasting
confidence: 50%
“…ALCAM overexpression significantly correlated with nodal involvement and tended to be associated with the presence of disseminated tumour cells in the bone marrow. Strong ALCAM expression also correlated with reduced recurrence and overall survivals in ductal carcinomas [119] Significant association was noted between ALCAM polymorphism (rs6437585T > C in ALCAM promoter) and risk of developing breast cancer in a Chinese population [135] IHC ALCAM staining intensity in tissue obtained from breast cancer metastasis (n = 117) was found to be higher in skin metastasis than in any other metastatic tissues examined (bone, liver, brain and lung), and ALCAM staining was also found to be higher in primary tumours which metastasised to the skin [136] Protein analysis of ALCAM expression in breast cancer patients (n = 150) indicated high expression of ALCAM at the membrane was associated with metastatic dissemination and lymph node metastasis, whereas increased ALCAM expression in the cytoplasm was associated with short-term local recurrence and shortened disease-free patient survival [137] Two SNPs within the ALCAM gene (re1044243 and rs1157) were associated with breast cancerspecific survival when analysed in a Swedish population-based series (n = 783) of breast cancer cases. However, no association was observed within a Polish population of familial/early-onset breast cancer cases (n = 506) [138] (continued) which could bind ALCAM on both cancer cell lines and in tumour tissues.…”
Section: Metastatic Potential Of Alcam and Clinical Implications In Bmentioning
confidence: 99%
“…Recently, ALCAM has also been shown to function in axonal growth of dorsal root ganglion neurons and to modulate neurotrophin signaling thereby regulating neurotrophin-dependent neurite outgrowth [ 287 , 288 ]. ALCAM has also been associated with multiple sclerosis susceptibility although the mechanism is controversially discussed [ 289 , 290 ].…”
Section: Structure and Functions Of Different Cell Adhesion Molecumentioning
confidence: 99%